Design and Pilot Processes for Enhancing Facilitation, Communication and Coordination of Innovation Platforms - International Livestock Research Institute (International Food Policy Research Institute, 2015)
Estabilishing platfroms at different levels, Regular Innovation Platform meetings, IP Facilitation Guidelines, Training on Facilitation, Coordination and Communiation for IP members, Farmers Field Day. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/innovation_platform_design